PENGARUH DEEP LEARNING MELALUI KUIS DIGITAL INTERAKTIF TERHADAP HASIL BELAJAR SISWA KELAS IV PADA MATERI NILAI-NILAI PANCASILA SD NEGERI PELANG LOR 1 - Arum Kusumawati, Gita; Aulia Fajar Khasanah; Nofita Lestariningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Deep Learning approach through contextual-based interactive digital quizzes on the learning outcomes of fourth-grade students on the Pancasila Values ​​material. The study used an experimental method with a pretest-posttest control group design. The study population was all fourth-grade students of Pelang Lor 1 Elementary School and Karangbanyu 1 Elementary School, with a sample of 26 students in the experimental class (Pelang Lor 1 Elementary School) and 26 students in the control class (Karangbanyu 1 Elementary School). The sampling technique used cluster random sampling. The research instrument was a written multiple-choice test of 25 questions that had been tested for validity and reliability. Data analysis techniques included the Shapiro-Wilk normality test, Levene's homogeneity test, paired sample t-test, and independent sample t-test. The results showed that the average posttest of the experimental class (81.08) was higher than the control class (77.81). The independent t-test yielded a t-value of -4.521 with a significance level of <0.001 (p <0.05), indicating a significant difference in learning outcomes between the experimental and control classes. The paired t-test in the experimental class also showed a significant increase from pretest to posttest with a gain of 12,885 points (p <0.001). Therefore, the alternative hypothesis (Ha) is accepted and the null hypothesis (H₀) is rejected. The conclusion of this study is that the Deep Learning approach through contextual-based interactive digital quizzes significantly impacts the learning outcomes of fourth-grade students on the topic of Pancasila Values. The implications of this study are expected to be an alternative innovative learning strategy for teachers and elementary schools.